Response of miR156-SPL Module during the Red Peel Coloration of Bagging-Treated Chinese Sand Pear (Pyrus pyrifolia Nakai) - Qian, Minjie; Ni, Junbei; Niu, Qingfeng; Bai, Songling; Bao, Lu; Li, Jianzhao; Sun, Yongwang; Zhang, Dong; Teng, Yuanwen (Frontiers in Physiology, 2017)
miR156 is an evolutionarily highly conserved plant micro-RNA (miRNA) that controls an age-dependent flowering pathway. miR156 and its target SQUAMOSA PROMOTER BINDING PROTEIN-LIKE (SPL) genes regulate anthocyanin accumulation in plants, but it is unknown whether this process is affected by light. Red Chinese sand pear (Pyrus pyrifolia) fruits exhibit a unique coloration pattern in response to bagging treatments, which makes them appropriate for studying the molecular mechanism underlying light-induced anthocyanin accumulation in fruit. Based on high-throughput miRNA and degradome sequencing data, we determined that two miR156 members (i.e., MIR156a and MIR156ba) were expressed in pear fruit peels, and targeted four SPL genes. Light-responsive elements were detected in the promoter regions of the MIR156a and MIR156ba precursors. We identified 19 miR156-targeted SPL genes using the ‘Suli’ pear (Pyrus pyrifolia Chinese White Pear Group) genome database, of which seven members were miR156 targets. The upregulated expression of anthocyanin biosynthetic and regulatory genes and downregulated expression of PpSPL2, PpSPL5, PpSPL7, PpSPL9, PpSPL10, PpSPL13, PpSPL16, PpSPL17, and PpSPL18 were observed in pear fruits after bags were removed from plants during the anthocyanin accumulation period. Additionally, miR156a/ba abundance increased after bags were removed. Yeast two-hybrid results revealed that the MYB10/bHLH/WD40 protein complex exists in pear, likely to regulate anthocyanin biosynthesis. Additionally, PpSPL10 and PpSPL13 interacted with PyMYB10. We propose the following model for miRNA-mediated light-induced anthocyanin accumulation in pear fruits: miR156 positively regulates light-induced anthocyanin biosynthesis by cleaving PpSPL genes to stabilize the MYB10/bHLH/WD40 protein complex, which is essential for activating the expression of anthocyanin biosynthetic genes.